2021
DOI: 10.1055/a-1640-3236
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic resection for superficial duodenal tumors: 10 years’ experience in 18 Japanese high volume centers

Abstract: Background and study aim: There is no enough data for endoscopic resection (ER) of superficial duodenal epithelial tumors (SDETs) due to its rarity. There are two main kinds of ER techniques for SDETs: EMR and ESD. In addition, modified EMR techniques, underwater EMR (UEMR) and cold polypectomy (CP), are getting popular. We conducted a large-scale retrospective multicenter study to clarify detailed outcomes of duodenal ER. Patients and methods : Patients with SDETs who underwent ER at 18 institutions from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 33 publications
2
82
1
1
Order By: Relevance
“…ESD is reported to accomplish secure en bloc resection for superficial epithelial tumors arising from the gastrointestinal tract irrespective of the size and location [11][12][13][14] . Similarly, duodenal ESD accomplishes higher en bloc resection rates in previous reports [15][16][17][18][19][20][21][22] . Moreover, a recent multicenter retrospective study including more than 3000 cases undergoing duodenal endoscopic treatment in Japan reported high duodenal ESD en bloc resection rates regardless of the size, location, or presence of fibrosis of the lesion, whereas other endoscopic resection techniques including endocopic mucosal resection (EMR) and underwater EMR revealed inferior resectability, especially for lesions larger than 20 mm [23] .…”
Section: Indications For Esd and Cure Criteriamentioning
confidence: 58%
See 1 more Smart Citation
“…ESD is reported to accomplish secure en bloc resection for superficial epithelial tumors arising from the gastrointestinal tract irrespective of the size and location [11][12][13][14] . Similarly, duodenal ESD accomplishes higher en bloc resection rates in previous reports [15][16][17][18][19][20][21][22] . Moreover, a recent multicenter retrospective study including more than 3000 cases undergoing duodenal endoscopic treatment in Japan reported high duodenal ESD en bloc resection rates regardless of the size, location, or presence of fibrosis of the lesion, whereas other endoscopic resection techniques including endocopic mucosal resection (EMR) and underwater EMR revealed inferior resectability, especially for lesions larger than 20 mm [23] .…”
Section: Indications For Esd and Cure Criteriamentioning
confidence: 58%
“…Miura et al [22] reported the effectiveness of the pocket creation method (PCM). In PCM, a small, tapered tip hood is used to create a pocket by dissecting the submucosa without a circumferential incision.…”
Section: Techniquementioning
confidence: 99%
“…6 Moreover, there were no significant differences in the incidences of intraprocedural perforation and delayed perforation between EMR and U-EMR. 6 In the study by Takatori et al, the incidence of delayed bleeding and intraoperative or delayed perforation of PI-UEMR was 2%, 2%, and 0%, respectively, with no significant differences compared with those of U-EMR. Thus, PI-UEMR has an acceptable safety level and should be confirmed in further studies.…”
mentioning
confidence: 84%
“…9 A recent large multicenter study also reported that the en bloc resection rate of U-EMR was significantly lower than that of conventional EMR for both lesion categories of 10-14 mm (81.5% vs. 91.3%, respectively) and 15-19 mm (62% vs. 74.4%, respectively). 6 One possible reason for the inferior performance of U-EMR for SDETs in en bloc resection is that distal margins are often obscured during snaring, especially for lesions on the duodenal folds.…”
mentioning
confidence: 99%
“…Meanwhile, ESD‐related perforation has significantly decreased due to the recent development of ESD devices and the establishment of improved therapeutic strategies 2 . However, current data from experienced endoscopists still show a certain incidence of perforation: 2.2% in the esophagus, 3 1.3% in the stomach, 4 9.3% in the duodenum, 5 and 2.7% in the colon 2 . Although the symptoms and severity associated with perforation differ depending on the size and location of the defect, the timing of its occurrence, the degree of contamination, and the patient’s condition, perforation is considered a severe adverse event.…”
mentioning
confidence: 99%